Structural phase transition and switchable dielectric behaviour of a one-dimensional chain niobium oxyfluoride. Issue 20 (11th May 2022) - Feng, Yan; Wang, Ze-Jie; Li, Long-He; Liao, Rong-Meng; Hu, Zhao-Bo; Li, Jian-Rong; Shi, Chao; Ye, Hen-Yun
Abstract : A one-dimensional inorganic organic hybrid niobium oxyfluoride undergoes a reversible phase transition and exhibits a switchable dielectric behavior. Abstract : Structural phase transition is always accompanied by measurable property changes in the material, which provides us more opportunities for material modification. Herein, a new niobium oxyfluoride, [HIm][NbOF4 ] (HIm = imidazole cation, compound 1 ), was obtained, and its structural phase transition behavior was investigated. The compound features a one-dimensional chain of anionic [NbOF4 ] n − connected by corner-sharing oxygen. It undergoes an obvious structural phase transition at 284 K, as confirmed by variable-temperature structural analyses, differential scanning calorimetry (DSC), and dielectric measurements. In particular, the reversibility of dielectric switching properties of 1 was identified around the phase transition point. This discovery will enrich the potential applications of niobium oxyfluoride in dielectric switching.